Art as Intervention in the Time of Chinese Social Transformation - Chunchen, Wang (Filozofski vestnik, 2016)
The article deals with the phenomenon of the alternative nature of contemporary Chinese art. Since in the past two decades contemporary art as a term has in general proved to be difficult to define, we should not forget the particular situation of Chinese artists – their social, cultural, and political situation – when facing and discussing contemporary art made by Chinese artists. It is only in such context that we can focus on, write about, and comment on the special characteristics of Chinese contemporary art. The article then discusses the transformative function of art as a kind of expressive means which is used and applied to different situations by Chinese artists. This new functionalism of art in China has a special significance and meaning in the light of China’s complicated social system. Our stake is that in this drastically changing period in China we should reconsider theory on socially meaningful art, instead of, for this period, the ordinary.